A Research Review of Literacy Tutoring and Mentoring in Initial Teacher Preparation: Toward Practices That Can Transform Teaching. (June 2019) - Hoffman, James V.; Svrcek, Natalie; Lammert, Catherine; Daly-Lesch, Annie; Steinitz, Erica; Greeter, Erin; DeJulio, Samuel
Our goal through this literature review is to report and synthesize the findings from research into literacy tutoring and literacy mentoring in initial teacher preparation. We identified a total of 62 published articles that met our selection criteria. We identified four conceptual areas of focus to organize and represent our findings: (a) the structural and design features of the one-to-one or small-group experiences, (b) preservice teacher learning and growth within the tutorial/mentoring experience, (c) preservice teacher learning and growth beyond the tutorial/mentoring experience, and (d) mediating factors associated with preservice teacher growth. We discuss the challenges and promises for this line of research for transforming teacher preparation through the attention to third and hybrid spaces for mentoring experiences.